Caffeic Acid Phenethyl Ester With Mesenchymal Stem Cells Improves Behavioral and Histopathological Changes in the Rat Model of Parkinson Disease - Khojasteh Rahimi Jaberi; Manouchehr Safari; Vahid Semnani; Hamid Reza Sameni; Sam Zarbakhsh; Laya Ghahari (Basic and Clinical Neuroscience, 2022)
Introduction: Parkinson disease (PD) results from the destruction of dopaminergic neurons in the brain. This study aimed to investigate the protective effects of natural antioxidants such as caffeic acid phenethyl ester (CAPE) to maintain these neurons. Methods: CAPE is one of the main ingredients of propolis. Intranasal administration of 1-methyl-4-phenyl-2;3;4;6-tetrahydropyridine (MPTP) was used to generate a PD model in rats. A total of 2×bone marrow stem cells (BMSCs) were injected from the tail vein. Behavioral tests, immunohistochemistry, DiI, cresyl fast violet, and TUNEL staining were used to evaluate the rats 2 weeks after treatment. Results: In all treatment groups with stem cells, the DiI staining method revealed that the cells migrated to the substantia nigra pars compacta after injection. Treatment with CAPE significantly protects dopaminergic neurons from MPTP. The highest number of tyrosine hydroxylase (TH) positive neurons was seen in the pre-CAPE+PD+stem cell (administration of CAPE, then the creation of PD, finally injection of stem cells) group. The number of TH+cells in all groups that received CAPE was significant compared to groups that received the stem cells only (P<0.001). Intranasal administration of MPTP significantly increases the number of apoptotic cells. The lowest number of apoptotic cells was in the CAPE+PD+stem cell group. Conclusion: The results showed that the use of CAPE and stem cells in Parkinson rats caused a significant reduction in the apoptotic cells.